ORGANIZATIONAL ASPECTS OF ECOLOGICAL AUDIT AS AN ELEMENT OF THE ENVIRONMENTAL PROTECTION SYSTEM (World Economics and Finance Bulletin, 2025)
The article examines the organizational aspects of environmental audit as an element of the environmental protection system. Conclusions are made, proposals and recommendations for improving the organization of environmental audit are developed.